Leveraging Quality Management and Partnership Programs for Technopreneurial Success: Exploring their Impact on MSME Performance - Muhammad Reza Aulia; Zulkarnain Lubis; Ihsan Effendi; Junaidi (Pandawan, 2023)
This research study explores the impact of leveraging quality management and partnership programs on the performance of micro, small, and medium enterprises (MSMEs) in the context of technopreneurship. The objective of this study is to analyze the relationship between knowledge, capital, partnership programs, and the performance of MSMEs assisted by PTPN III. The study involved MSME business actors who received assistance from PTPN III. The research methodology employed quantitative analysis, with data collected through surveys and analyzed using statistical techniques. The findings of this study indicate that capital has a significant influence on the partnership program and the performance of MSMEs. However, knowledge does not show a significant impact on the partnership program and MSME performance. Moreover, the partnership program itself has a significant positive effect on MSME performance. Additionally, the partnership program mediates the relationship between knowledge, capital, and MSME performance. These results suggest that providing adequate capital resources and implementing effective partnership programs are crucial for enhancing the performance of MSMEs in the technopreneurship sector. Furthermore, the study highlights the importance of developing comprehensive strategies that integrate knowledge, capital, and partnership programs to drive the success of MSMEs. Overall, this research contributes to the understanding of the factors influencing technopreneurial success and provides insights for policymakers, MSME support organizations, and entrepreneurs themselves in developing strategies to optimize the performance of MSMEs in the rapidly evolving technopreneurship landscape.